Anti-Cancer Cytotoxic Effects of Multiwalled Carbon Nanotubes - Garcia-Hevia, Lorena; Valiente, Rafael; Gonzalez, Jesus; Luis Fernandez-Luna, Jose; C. Villegas, Juan; L. Fanarraga, Monica (Current Pharmaceutical Design, 2015)
Recent research has opened new alternatives to traditional chemotherapy treatments using nanomaterials as cytotoxic agents. Anti-cancer nanomedicines do not require specific target sites on key proteins or genes to kill cancer cells and have radically different mechanisms to interact with the living matter. Among 1D nanomaterials, multiwalled carbon nanotubes (MWCNTs) have the intrinsic ability to bind tubulin and interfere with microtubule dynamics, mimicking the effect of traditional cytotoxic microtubule-binding agents such as paclitaxel (taxol®). Here, we review the cytotoxic properties of MWCNTs and show a direct pro-apoptotic effect of these nanomaterials in vitro in different cancer cell lines and tumor cells obtained from surgical specimens. Understanding the bio-synthetic relationship between MWCNTs and microtubules could serve to improve these nanomaterials to be used as broad spectrum antineoplastic agents in combination to traditional microtubule-binding treatments, thus avoiding drug resistance mechanisms in cancer cells.
Keywords: microtubule dynamics